Effectiveness of the multi-component intervention 'Focus' on reducing smoking among students in the vocational education setting: a cluster randomized controlled trial - Simone G. Kjeld; Lau C. Thygesen; Dina Danielsen; Gitte S. Jakobsen; Marie P. Jensen; Teresa Holmberg; Lotus S. Bast; Lisbeth Lund; Charlotta Pisinger; Susan Andersen (BMC, 2023)
Abstract Background Social inequality in smoking remains an important public health issue. Upper secondary schools offering vocational education and training (VET) comprise more students from lower socioeconomic backgrounds and have higher smoking prevalence than general high schools. This study examined the effects of a school-based multi-component intervention on students' smoking. Methods A cluster randomized controlled trial. Eligible participants were schools offering VET basic courses or preparatory basic education in Denmark, and their students. Schools were stratified by subject area and eight schools were randomly allocated to intervention (1,160 invited students; 844 analyzed) and six schools to control (1,093 invited students; 815 analyzed). The intervention program comprised smoke-free school hours, class-based activities, and access to smoking cessation support. The control group was encouraged to continue with normal practice. Primary outcomes were daily cigarette consumption and daily smoking status at student level. Secondary outcomes were determinants expected to impact smoking behavior. Outcomes were assessed in students at five-month follow-up. Analyses were by intention-to-treat and per protocol (i.e., whether the intervention was delivered as intended), adjusted for covariates measured at baseline. Moreover, subgroup analyses defined by school type, gender, age, and smoking status at baseline were performed. Multilevel regression models were used to account for the cluster design. Missing data were imputed using multiple imputations. Participants and the research team were not blinded to allocation. Results Intention-to-treat analyses showed no intervention effect on daily cigarette consumption and daily smoking. Pre-planned subgroup analyses showed statistically significant reduction in daily smoking among girls compared with their counterparts in the control group (OR = 0.39, 95% CI: 0.16, 0.98). Per-protocol analysis suggested that schools with full intervention had higher benefits compared with the control group (daily smoking: OR = 0.44, 95% CI: 0.19, 1.02), while no marked differences were seen among schools with partial intervention. Conclusion This study was among the first to test whether a complex, multicomponent intervention could reduce smoking in schools with high smoking risk. Results showed no overall effects. There is a great need to develop programs for this target group and it is important that they are fully implemented if an effect is to be achieved. Trial registration https://www.isrctn.com/ISRCTN16455577 , date of registration 14/06/2018.